1994
DOI: 10.3382/ps.0730587
|View full text |Cite
|
Sign up to set email alerts
|

Feed Gorging and Extended Water Restriction Do Not Produce Knockdown in Male Turkeys Fed Monensin

Abstract: A study was conducted to determine the effects of feed restriction with subsequent gorging during extended water restriction on 27- to 57-d-old toms fed excess monensin. Four treatments were factorially arranged with two levels of dietary monensin (0 and 140 ppm) and two feeding-watering regimens (ad libitum and restricted). Ad libitum birds had full access to feed and water but restricted birds only had access to feed from 0800 to 1200 h daily. A 24-h water restriction regimen was imposed biweekly from 28 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…This study confirms previous observations that the early short-term administration of antibiotics or MON in the recommended doses does not compromise the growth performance of birds ( Watkins et al, 1993 ; Watkins and Novilla, 1994 ; Chapman and Saleh, 1999 ; Sureshkumar et al, 2013 ). However, Madubuike et al (2020) reported that DOX administered in early life to vaccinated chickens decreased their BW gain.…”
Section: Discussionsupporting
confidence: 91%
“…This study confirms previous observations that the early short-term administration of antibiotics or MON in the recommended doses does not compromise the growth performance of birds ( Watkins et al, 1993 ; Watkins and Novilla, 1994 ; Chapman and Saleh, 1999 ; Sureshkumar et al, 2013 ). However, Madubuike et al (2020) reported that DOX administered in early life to vaccinated chickens decreased their BW gain.…”
Section: Discussionsupporting
confidence: 91%